Housing collateral and the monetary transmission mechanism - Karl Walentin; Peter Sellin (Sveriges Riksbank, 2010)
In this paper our main aim is to quantify the role that housing collateral plays for the monetary transmission mechanism. Furthermore, we want to explore the implications of the increase in household indebtedness, and specifically the loan-to-value ratio, in the last two decades. We set up a two sector DSGE model with production of goods and housing. Households can only borrow by using their houses as collateral. The structure of the model closely follows Iacoviello and Neri (2010). To be able to do quantitatively relevant exercises we estimate the model using Bayesian methods on Swedish data for 1986q1-2008q3. We quantify the reinforcement of the monetary transmission mechanism that housing used as collateral implies in the presence of nominal loan contracts. This mechanism functions through the effects of the interest rate on house prices as well as on inflation and thereby the real value of nominal debt. This component of the monetary transmission mechanism becomes stronger the higher the loan-to-value ratio is. A change in the maximum loan-to-value ratio from 85% to 95%, all else being equal, implies that the effect of a monetary policy shock is increased by 4% for inflation, 8% for GDP and 24% for consumption. We conclude that to properly understand the monetary transmission mechanism and its changing nature over time, we need to take into account the effects of housing related collateral constraints.
Keywords: E21; E32; E52; R21; R31; 330; house prices; residential investments; monetary policy; monetary transmission mechanism; collateral constraints; Bayesian estimation; Immobilienpreis; Wohneigentum; Geldpolitische Transmission; Geldpolitik; Bayes-Statistik; Schweden